Relación entre adhesión a la medicación y alfabetización em salud en personas ancianas (Research, Society and Development, 2020)
This study aimed to verify whether there is a relationship between medication adherence and health literacy in elderly people attending the Family Health Strategy of the western zone of a municipality in southern Brazil. A cross-sectional exploratory-descriptive, quantitative study of 17 family health teams with 350 elderly people, applying a Portuguese version of the Morisky Medication Adherence Scale, which verified the degree of adherence to the medication and a translated version of the Short-Test of Functional Health Literacy in Adults, which verified the degree of health literacy. A descriptive and inferential statistical analysis was performed. It was verified that 224 (64%) participants were considered non-adherent to the medication, and 206 (58.9%) had inadequate literacy, and there was no significant association between these variables. Participants reported other difficulties in drug treatment, among them, forgetfulness had a significant relationship with adherence. The lack of understanding of health information did not influence adherence to the medication treatment of the participants. Professionals must pay attention to other difficulties that may arise, especially forgetfulness, listing strategies aimed at minimizing it, such as monitoring and monitoring drug treatment.